Clostridial C3 Toxins Target Monocytes/Macrophages and Modulate Their Functions - Barth, Holger; Fischer, Stephan; Möglich, Amelie; Förtsch, Christina (Frontiers in Immunology, 2015)
The C3 enzymes from Clostridium (C.) botulinum (C3bot) and C. limosum (C3lim) are single chain protein toxins of about 25 kDa that mono-ADP-ribosylate Rho A, -B, -C in the cytosol of mammalian cells. We discovered that both C3 proteins are selectively internalized into the cytosol of monocytes and macrophages by an endocytotic mechanism, comparable to bacterial AB-type toxins, while they are not efficiently taken up into the cytosol of other cell types including epithelial cells and fibroblasts. C3-treatment results in disturbed macrophage functions such as migration and phagocytosis, suggesting a novel function of clostridial C3 toxins as virulence factors, which selectively interfere with these immune cells. Moreover, enzymatic inactive C3 protein serves as a transport system to selectively deliver pharmacologically active molecules into the cytosol of monocytes/macrophages without damaging these cells. This review addresses also the generation of C3-based molecular tools for experimental macrophage pharmacology and cell biology as well the exploitation of C3 for development of novel therapeutic strategies against monocyte/macrophage-associated diseases.